Avaliação da concordância entre os testes tuberculínico e o QuantiFERON®-TB Gold in tube no diagnóstico da infecção latente pelo Mycobacterium tuberculosis em crianças e adolescentes - Boni, Patrícia Marques Rodrigues (2015)
Background: One of the main characteristics of M. tuberculosis (Mtb) is its capacity to produce latent infection. The World Health Organization (WHO) estimates that 2 billion people are infected by this bacillus, only 10% of whom develop active disease. Until recently the tuberculin skin test (TST) was the only test available for the diagnosis of latent infection. However, because of its potential limitations an effort was made to develop a more accurate method to diagnose latent tuberculosis. The interferon-gamma release assays (IGRA’s) were the result. These tests measure the interferon-gamma production by T-lymphocytes in response to a challenge of three synthetic antigens, specific for Mtb (ESAT-6, CFP-10 e TB7.7). The objective of our study was to evaluate the performance of the TST and the QuantiFERON®-TB Gold assay-in-tube (QFT-GIT), for the diagnostic of latent Mtb infection in children and adolescents identified as household contacts of smear positive pulmonary Mtb index cases. Methods: This was a comparative study conducted in the Metropolitan area of Vitória, Espírito Santo, Brazil from March 2008 through October 2013. Clinical, demographic and epidemiological data were collect from all participants. We defined latency as a positive TST (induration ≥ 10mm) or a positive QFT-GIT test (Nil ≤8.0 IU/ml, TB Antigen minus Nil ≥0.35 IU/ml and ≥25% of Nil value). Both tests were performed in each volunteer between eight and ten weeks after the identification of the respective index cases. Concordance, as defined by kappa testing, was used to compare the results of the two methods of diagnosing latency. The factors associated with positivity of both tests in bivariate analysis (p ≤0.30) were included in the multivariate model (logistic regression), and the odds ratios (OR) and 95%CI were calculated. Results: 291 subjects were enrolled in the study. The global concordance between TST and QFT-GIT was high (87,6%) - k 0.75 [CI 95%: 0.63- 0.86]. However in children age ≤ 5 years the concordance was even higher (93.65%) - κ 0.87 [CI 95%: 0,63-1,12]. The presence of BCG scar was not statistically associated with tests positivity. There was a positive correlation between the size of TST induration and the probability of a positive QFT-GIT. Conclusion: There was no advantage in the use of QFT-GIT in relation to the TST. We recommend the twomonth timeframe after the identification of the index case to perform the tests in the household contacts.